Secuelas Musculoesqueléticas en pacientes con aislamiento domiciliario post Covid-19. Una mirada desde la Fisioterapia: Musculoskeletal sequelae in symptomatic patients Postcovid-19. A look from Physiotherapy (La U Investiga, 2020)
The SARS-CoV2 (COVID-19) viral infection is a global threat that already affects more than 10 million people worldwide and associates variable mortality depending on the country. The Pan-American Health Organization informed that the main sequels left by the virus are an intense inflammation in the respiratory tract, as well as in the cardiovascular, musculoskeletal and nervous systems.The objective of this study was to describe the persistent clinical characteristics in the musculoskeletal system, of patients with confirmation of coronavirus disease (COVID-19), who have overcome the disease and have been treated in home isolation. A qualitative, transversal study was carried out, with a descriptive approach, for the collection of the information, it was made with a standardized questionnaire, whichwas validated by experts’ judgment. The sample was made up of 50 patients, who met the criteria for inclusion and exclusion. Among the main results it was found that 52% of the patients were male with a median age of 43 years and 48% belonged to the female gender with a median age of 42 years. 44% of the patients presented at least one comorbidity, 14% were completely free of any symptom related to COVID-19,while 34% had 1 or 2 sequelae and 56% had 3 or more sequelae. The most prevalent sequel was muscle fatigue detected in 27 patients, followed by generalized weakness with 46% and myalgias with 16%.
Keywords: secuelles Covid-19; physiotherapy; musculoskeletal disorders